CO-RELATIONAL STUDY OF THE EXTENT OF INTRINSIC/EXTRINSIC MOTIVATION TO CODE SWITCHING ON FACEBOOK - Rabia Sohail; Nazir Ahmed Malik (European Scientific Journal, ESJ, 2014)
The people, who switch code, are divided on the basis of their intrinsic or extrinsic motivational scores. This division helps in recognizing the direct agents of language change. It also helps in identifying people’s behavior towards language on the basis of their motivational pattern.30 intrinsically and extrinsically motivated people of society of age from 15 to 40 years are selected through convenient sampling. Their motivation level is estimated through a specifically designed questionnaire. Along with Facebook data a questionnaire has served the purpose of measuring the participants’ motivation level. To co-relate these two variables of motivation and code switching, the scores were compared and co-relational coefficient was calculated. The results show that higher level of motivation; extrinsic or intrinsic shows least Code switching as correlation was found in both groups. Further examination revealed that intrinsically motivated participants show uniform behavior of least code switching and more use of English with the higher score of motivation whereas in extrinsically motivated group this trend is not clear as there are participants who exhibit varied responses. The participants who are motivated in both ways who have no clear distinctive motivational behavior are usually undecided and they do more code switching. Moreover female participants are more intrinsically motivated than male participants. The co-relational coefficient shows that the study was successful in finding a relation between the two variables.